Invasion risk assessment using trait-environment and species distribution modelling techniques in an arid protected area: Towards conservation prioritization. (October 2021) - El-Barougy, Reham F.; Dakhil, Mohammed A.; Halmy, Marwa W.; Gray, Sarah M.; Abdelaal, Mohamed; Khedr, Abdel-Hamid A.; Bersier, Louis-Félix
Highlights: Trait-environment and distribution models are tools for invasion risk assessment. Salvia rosmarinus, Eucalyptus globulus & Acacia saligna are invasion indicators. Assessing invasion risk at microhabitat scale is strong tool for local conservation. Wadis in SKP are threatened by invasion risk, they are priority conservation areas. An increase in precipitation & temperature seasonality indicates high invasion risk. Abstract: Invasive species are considered as one of the key threats to biodiversity and human livelihoods globally. The most effective strategy for handling invasion would be based on profiling invasive species and identifying areas at risk of invasion before they occur. The current study used a trait-environment modelling approach to identify alien species with high probability of invasiveness and combined this with the species distribution models (SDMs) to predict areas in the arid Saint Katherine Protectorate (SKP) in Egypt that were at highest risk of invasion by these species. The specific leaf area, number of leaves, soil nitrogen, and prevalence of disturbances were the most important biotic and abiotic indicators for predicting invasiveness in SKP. Of the investigated 33 alien plant species, three species were identified to have the highest probability of invasiveness, including Salvia rosmarinus, Eucalyptus globulus, and Acacia saligna . The outcome of the SDMs revealed that precipitation seasonality and temperature-related variables were the most important bioclimatic predictors determining the potential invasion risk of the studied alien species. Potential invasion is more likely in the eastern and northern parts of SKP, where biodiversity-rich common microhabitats are found and where there is a prevalence of disturbances such as tourism activities. The Etalaa, Shaq Mosa, and El-Mesirdi wadis microhabitats, in particular, were identified in the current study to be potentially highly suitable microhabitats for alien invasiveness and should be prioritized for monitoring and conservation actions. Moreover, the three identified species could be used as early indicators for microhabitats at risk of invasion along the environmental gradients of temperature and precipitation in arid ecosystems. This approach can be applied to other taxa and other ecosystems and can provide opportunities for formulating proactive management strategies against biological invasions.